Development of Fabric Surface Texture and Design Natural Dyed Hand-Woven Patterns in the Northern Regio - Komonsirichok, Yanisa; Sutakcom, Oranoot; Mitpaeng, Tayanit (Community and Social Development Journal, 2024)
This article aims to 1) Study the potential production, structure and consumer demand of hand-woven products with natural dyed fabric. 2) Develop the surface texture of fabric and design patterns of hand-woven fabrics that are suitable for textile manufacturing and meet the lifestyle of consumers. 3) Produce the prototypes of hand-woven fabrics which developed surface texture and pattern. 4) Assess consumer satisfaction with prototype product. The target group of this study is entrepreneurs of hand-woven fabrics using natural dyes in the northern region, there are 5 groups with 110 people in total, including the Ampan cotton group, Dao Mang Hemp Fabric Community Enterprise Group, Ban Pa Ngiu Karen Weaving Group, Ban Na Hang Karen Weaving Group, and Ban Huai Ta Community Enterprise Group. The research methods utilized in this study were focus groups, questionnaires, and collaboration with community entrepreneurs in developing and producing woven fabrics. The results show that the 15 woven fabrics developed by the researcher had better surface textures, with a soft touch and good recovery against wrinkles. Additionally, the new weaving structures resulted in new patterns. The researchers designed and produced 21 styles of contemporary casual wear, folk costume, and dress, which meet the requirements of consumers who value eco-friendliness, culture, healthy lifestyles, and minimalism. Furthermore, textile products such as bags, satchels, and hats were also designed and produced, emphasizing the fineness of sewing and the community product standards. Finally, the satisfaction of consumers with the prototype products was assessed, with an average satisfaction level of 4.84 out of 5.